2021
DOI: 10.1016/j.molmet.2021.101339
|View full text |Cite
|
Sign up to set email alerts
|

The Ile191Val is a partial loss-of-function variant of the TAS1R2 sweet-taste receptor and is associated with reduced glucose excursions in humans

Abstract: Objective Sweet taste receptors (STR) are expressed in the gut and other extra-oral tissues, suggesting that STR-mediated nutrient sensing may contribute to human physiology beyond taste. A common variant (Ile191Val) in the TAS1R2 gene of STR is associated with nutritional and metabolic outcomes independent of changes in taste perception. It is unclear whether this polymorphism directly alters STR function and how it may contribute to metabolic regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Postprandial hyperglycemia significantly contributes to total daytime hyperglycemia and strongly correlates with HbA 1c ( 30 ). This finding is aligned with the reduced OGTT glucose excursions seen in metabolically healthy lean Val/_ participants ( 10 ). However, we did not observe a direct genotype effects in glucose or insulin responses during an OGTT.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Postprandial hyperglycemia significantly contributes to total daytime hyperglycemia and strongly correlates with HbA 1c ( 30 ). This finding is aligned with the reduced OGTT glucose excursions seen in metabolically healthy lean Val/_ participants ( 10 ). However, we did not observe a direct genotype effects in glucose or insulin responses during an OGTT.…”
Section: Discussionsupporting
confidence: 75%
“…Taken together these observations suggest that, like in mice, TAS1R2 may have functional roles in peripheral tissues beyond taste perception. We recently used biochemical approaches to show that the Ile191Val substitution causes a partial loss-of-function of TAS1R2 by reducing the availability of the STR dimer in the plasma membrane ( 10 ). Healthy lean Val carriers had reduced glucose excursions during an OGTT ( 10 ), which resembles the effects seen in mice with a genetic loss-of-function of TAS1R2 ( 5 , 27 ), confirming that the Val substitution causes a partial loss-of-function of STRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweet taste sensing and signaling requires the formation of a T1R2/T1R3 heterodimer [ 14 , 41 ]. Although the mRNA expression of T1r2 and T1r3 has been previously reported in whole mouse islets [ 8 , 9 ], commercially available antibodies targeting STR are not specific.…”
Section: Discussionmentioning
confidence: 99%
“…Serrano et al. subsequently found that T1R2 gene variant Ile191Val causes a partial loss of function and results in reduced glucose excursions during an OGTT, which is independent of the variations in beta-cell function or insulin sensitivity ( Serrano et al., 2021 ). Additionally, bitter taste receptors have also been revealed of the function to evoke airway smooth muscle relaxation via localized calcium flux, predicting the potential role in counteracting asthmatic bronchoconstriction ( Deshpande et al., 2010 ).…”
Section: Regulation Of Taste Receptors On Oral Microbiota-host Intera...mentioning
confidence: 99%